Pendalaman Konten Kesehatan Mental dan Optimalisasi Komunikasi melalui Penyuluhan Berbasis Media untuk Kader Kesehatan dalam Penanggulangan Stunting di Desa Bangsalsari - Riskha Dora Candra Dewi; Muhammad Syirodj Arvany; Nisa, Rahmania Chairin; Mayfida Distinabila (Lembaga Pengembangan Kinerja Dosen, 2025)
Stunting prevention requires a comprehensive approach by involving various aspects such as mental health and effective communication. This article was prepared to find out more about the importance of mental health and effective communication with media-based counseling for health cadres as an effort to overcome Stunting. This media-based counseling activity was conducted on June 28-29, 2024, at the Community Welfare Empowerment Room or called PKK Bangsalsari Village Office. This article explains that the use of media as a counseling tool is considered effective in conveying information because the presentation is more interesting and easy to understand. After the activity, it can be concluded that the integration of mental health in Stunting prevention programs and the optimization of media-based communication are important strategies that need to be developed.